Strategic management process, content and implementation - Macmillan, Hugh; Tampoe, Mahen (Oxford University Press, 2000)
Gives a structured balanced summary of the important concepts in the field of strategic management. This work examines how these concepts may be effectively applied in practice, giving special attention to demonstrating the significance of the role of people in strategy implementation.